(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study based on the correlation coefficient study of insect pest in accordance with meteorological parameters on green gram (Vigna radiata). The data were taken from an experiment which was conducted by Entomology Department at Breeding Seed Production unit of Plant Breeding and Department, JNKVV Jabalpur M.P. In the experiment there are 3 replications each consist 13 treatments, from each treatment 10 plants were selected randomly and tagged for the recording of the number of major insect pests consists larvae insects (whitefly, leaf hopper, aphid, spodoptera litura and blue butterfly). Thus overall, 390 plants were selected and the data were recorded once in a standard week. Treatment details T1-TM-37, T2- TJM-160, T3- TJM-196, T4- Sikha, T5- PDM-139, T6- TJM-140, T7- Virat, T8- TM-115, T9- TJM-141, T10-TJM-136, T11-TJM-111, T12- TJM-155, T13- TJM-137.